Islamic Law, the State, and Human Rights: The Contestation of Interfaith Marriage Discourse on Social Media in Indonesia - Y Sonafist; Henny Yuningsih (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aimed at explaining the contestation of interfaith marriage discourse on social media, specifically on Instagram. The issue of interfaith marriage was quickly responded by social media users, not only by posting on their own accounts, but also by commenting on those posts of other people’s accounts. This study attempted to map Instagram media users’ comments on posts about interfaith marriage and to see the contestation of these comments in the context of the discourse on Islamic law, the state, and human rights in Indonesia. Qualitative research method was used in conducting this study. Data were collected from netizens’ comments on the issue of interfaith marriage, specifically the issue of interfaith marriage conducted by a member of Presidential Special Staff, the District Court’s decision on granting the interfaith marriage, and the Supreme Court’s circular on interfaith marriage. These comments were randomly selected and then analyzed using qualitative content analysis methods. This study found that: first, there were two response models for social media users when commenting on the issue of interfaith marriage on Instagram, they were the responses of acceptance and rejection. The narrative of the comments that accepted the idea of interfaith marriage emphasized human rights, diversity, freedom, and criticized the state’s involvement in private matters. Meanwhile, the narrative of comments that rejected the idea of interfaith marriage mostly refered to the provisions of Islamic law and state law. Second, based on these two response models, there was a contestation over the discourse of interfaith marriage in the context of Islamic law, the state, and human rights. However, this contestation was not based on a deep understanding of human rights and legal discourse. This contestation might have an impact on the public’s lack of legal understanding of interfaith marriage and had the potential to cause conflict on social media. This study confirmed that contestation of legal discourse came not only from people who had authority, but also from people who did not have in-depth legal knowledge.